2010
DOI: 10.1016/j.neuron.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Human Brain Evolution: Harnessing the Genomics (R)evolution to Link Genes, Cognition, and Behavior

Abstract: The evolution of the human brain has resulted in numerous specialized features including higher cognitive processes, such as language. The combination of our newfound communication expertise together with the process of transgenerational evolution at the epigenetic level has led to an exponential increase in human knowledge and abilities. In balance with these beneficent attainments though, the human brain has also acquired vulnerabilities to neuropsychiatric and neurodegenerative diseases, which reflect genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 164 publications
(199 reference statements)
3
28
0
Order By: Relevance
“…Over 100 different anatomical structures are connected by billions of neurons and glia into a functional network that regulates tissue homeostasis throughout the body while also determining our cognitive state (Nolte, 2009). Functionally distinct anatomical regions have evolved in a species-specific manner, giving rise to the defining physical and cognitive features that separate humans from other species (Konopka and Geschwind, 2010). Microarray analyses on distinct regions of the human brain have demonstrated that gene expression profiles vary significantly across adult brain structures (Colantuoni et al, 2011;Hawrylycz et al, 2012;Kang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Over 100 different anatomical structures are connected by billions of neurons and glia into a functional network that regulates tissue homeostasis throughout the body while also determining our cognitive state (Nolte, 2009). Functionally distinct anatomical regions have evolved in a species-specific manner, giving rise to the defining physical and cognitive features that separate humans from other species (Konopka and Geschwind, 2010). Microarray analyses on distinct regions of the human brain have demonstrated that gene expression profiles vary significantly across adult brain structures (Colantuoni et al, 2011;Hawrylycz et al, 2012;Kang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have uncovered that the pattern of gene co-expression is a critical mediator of brain function and exhibits significantly different patterns across species. 43 Gene pairs that have strong co-expression relationships are more likely to be functional together; therefore such analysis of co-expression networks in the brain among primates has proven informative. For example, weighted gene co-expression network analysis has been used to identify human-specific networks of gene expression compared with chimpanzees.…”
Section: Differences In Co-expression Networkmentioning
confidence: 99%
“…ing up empty handed [Konopka and Geschwind, 2010]. Therefore, the contribution of potential genomic mechanisms to human brain uniqueness still remains mostly unknown.…”
mentioning
confidence: 99%
“…As previously predicted [King and Wilson, 1975], we are therefore left with differential regulation of gene expression in the human lineage as a potential major evolutionary force driving human cognition. The recent advent of microarrays and next generation sequencing technologies have allowed us to compare gene expression in the brains of humans and other species at a genomewide level [Konopka and Geschwind, 2010]. However, the identification of a few hundred genes differentially expressed between human and non-human primate brain [Caceres et al, 2003] is unlikely in itself to explain the higher cognition in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation